Amerykańska praktyka renditions jako współczesny przykład wymuszonych zaginięć: [American practice of renditions as a contemporary example of enforced disappearances] (Studia Prawnicze / The Legal Studies, 2009)
Zjawisko wymuszonych zaginięć sięga czasów II wojny światowej, kiedy to A Hitler w zarządzeniu z dnia 7 grudnia 1941 r. (tzw. Dekret „Noc i mgła”) nakazał deportację z okupowanych terenów do Niemiec osób podejrzanych o opór przeciwko okupacji niemieckiej. W ramach tej akcji ok. 7000 osób, głównie Francuzów zostało skazanych na śmierć przed sądami specjalnymi bądź osadzonych w obozach koncentracyjnych. Wiele osób zostało potajemnie przetransportowanych do Niemiec, gdzie ślad po nich zaginął. Podobne metody były stosowane w państwach Ameryki Południowej przez reżimy wojskowe rządzące w latach 60-tych i 70-tych ubiegłego wieku (Gwatemala, Chile, Argentyna). Wtedy też po raz pierwszy został użyty termin wymuszone zaginięcie {enforced disappearance) będący tłumaczeniem z języka hiszpańskiego desapańcion forzada. Wśród państw, w których miały miejsce wymuszone zaginięcia można wymienić inter alia: Algierię, Argentynę, Chile, Chiny, Cypr, Etiopię, Filipiny, Honduras, Indie, Indonezję, Iran, Irak, Jemen, Gwatemalę, Kolumbię, Kongo, Liban, Meksyk, Maroko, Nepal, Nikaraguę, Peru, Rosję (Czeczenia), Salwador, Stany Zjednoczone, Sudan, Sri Lankę, Timor-Leste czy Turcję After a short historical introduction of the phenomenon of enforced disappearances, the author analyzes it from the point of view of international human rights law on the one hand and international humanitarian law on the other. Enforced disappearance is one of the most serious violations of human rights, very often described as the infringement of human dignity. Enforced disappearance is not a simple violation but a multiple one which means that it infringes several human rights including many non-derogable (the right to life, freedom from torture and other cruel, inhuman or degrading treatment, the right to recognition everywhere as a person before the law). The characteristic feature of this crime comprises the fact that the victim is devoid of any legal protection and the authorities deny having her or him under control; thus they refuse the victim any rights, in particular a right to a fair trial. The article contains analysis of the following human rights law instruments aimed at protection from enforced disappearances: the UN General Assembly Declaration on the Protection of all Persons from Enforced Disappearance (1992) and the UN Convention for the Protection of all Persons from Enforced Disappearance (2006). It also mentions the Statute of the International Criminal Court (1998) and Inter-American Convention on Forced Disappearance of Persons (1994). The second part-dedicated to international humanitarian law-presents provisions relevant to the protection from enforced disappearances. They are to be found especially in the four Geneva Conventions of 1949 and their Additional Protocols of 1977 which however do not use the term enforced disappearance. Those provisions relate inter alia to the search for and collecting the wounded and sick, recording and forwarding of information, the right of the prisoners of war to send and receive letters and cards, preparation of the wills, death certificates, burial, cremation of the prisoners of war and a Central Prisoners of War Information Agency whose function is to collect all the information it may obtain through official or private channels respecting prisoners of war, and to transmit it as rapidly as possible to the country of origin of the prisoners of war or to the Power on which prisoners depend. Taking this into account the author next explains the contemporary example of enforced disappearances namely American renditions or extraordinary renditions undertaken during the so called “war on terrorism”. Renditions meet all the legal conditions of enforced disappearances which the author tries to prove.